Optimasi Dosis Pupuk Organik dan NPK Majemuk pada Tanaman Kelapa Sawit Belum Menghasilkan - Siallagan, Irwan; ,, Sudradjat; ,, Hariyadi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2014)
ABSTRACTOptimum fertilization is not only proposed for obtaining desireable quality and quantity of the plant, but also to avoid excess fertilizer causing toxicity and environmental damage. The objective of this research  was to study and to determine an optimum rate of organic and NPK compound fertilizers for immature oil palm. The experiment was carried out at IPB-Cargill  Oil palm Teaching Farm, Jonggol, from March 2013 to March 2014. The treatments was laid out in a factorial randomized complete block design with three replications. The first factor was organic fertilizer,  i.e. 0, 15, 30 and 45 kg organic fertilizer plant-1, and the second was NPK compound fertilizer, i.e. 0, 0.65, 1.3, 1.95 and  2.6 kg NPK compound fertilizer plant-1. The result  showed  that vegetative growth increases  with fertilizer application. The height and stem girth of  plant were significantly affected by interaction between organic and NPK compound fertilizers, however there was no significant effect on frond production, frond length and leaf area. N, P leaf content of  plant were affected by interaction between organic and NPK compound fertilizers, however there was no effect on K leaf content, chlorophyll and number of stomata. Based on the height and stem girth regression equation, the optimum recommendation rate of organic and NPK compound fertilizers for immature first year oil palm are 40.7 kg organic fertilizer plant-1 and 1.9 kg NPK compound plant-1 Keywords: inorganic fertilizers, nutrient level, stem girth, vegetative growth